2007
DOI: 10.1111/j.1365-2044.2007.05358_2.x
|View full text |Cite
|
Sign up to set email alerts
|

A reply

Abstract: quantified using data envelopment analysis [3]. The caseload of each specialty at each hospital is a valid [4] and useful [5] end-point to determine if more workload for each specialty can be achieved at each hospital based on hospital and census data [6]. Results comparing scores of hospitals can be summarised in tabular and graphical format for managers [6,7] and integrated into OR block time decisions [6,8].We challenge Pandit et al. to show corresponding validity [4,6] and usefulness [5,7,8] of their measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It also aims to stimulate and motivate the achievement of students in interdisciplinary studies (Kusmaryono, 2014). There are many students who are indifference towards learning mathematics from school level to university level (Pandit, 2007). In context of Nepal, Similarly, ERO (2013) found that SLC dropouts struggle with Mathematics, English, and Science.…”
Section: Introductionmentioning
confidence: 99%
“…It also aims to stimulate and motivate the achievement of students in interdisciplinary studies (Kusmaryono, 2014). There are many students who are indifference towards learning mathematics from school level to university level (Pandit, 2007). In context of Nepal, Similarly, ERO (2013) found that SLC dropouts struggle with Mathematics, English, and Science.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above mentioned fact, many students contemplate mathematics as a difficult subject (Yadav, 2017) and are indifference towards learning mathematics in each level from university to school (Pandit, 2007). In context of Nepal, series of studies conducted by education review office (ERO) on students achievements in mathematics indicate a consistent trends of poor achievements at school level and students' failed in school leaving certificate examination in three core subjects viz mathematics, science and English.…”
Section: Introductionmentioning
confidence: 99%